Research on anti UAV swarm system in prevention of the important place. (April 2020) - Hao, Q; Li, W Z; Qiu, Z K; Zhang, J L
Abstract: With the rapid development of artificial intelligence (AI) technology, UAV swarm has become possible. It has become an urgent problem that how to realize the effective counteraction to the UAV swarm in the important target security defence, or in the important place prevention in the war. In this paper, by analysing the development status and combat characteristics of UAV swarm, as well as existing anti-UAV technology, the countermeasures and technologies applicable to UAV swarm is combed. Then the further construction of anti UAV swarm control system is built to realize the effective anti UAV swarm in the key prevention and control.